Integrating Network, Cad and VR into the Design and Development of Web-Based Computer Graphics Learning Materials - Sung, Wen-Tsai; Ou, Shih-Ching (Malaysian Journal of Computer Science, 2001)
The purpose of this research is to apply the principle of constructivism to the design of Web-based training systems for teachers and learners. Several issues will be addressed in this paper including the development of a Web-based Interactive Design Graphics (WebDeGrator) to create a better learning environment. In this paper, we discuss the development of a web-based learning system to simulate and adjust computer graphics through BÃ©zier, B-spline and NURBS algorithms. The features of Computer-Aided Design (CAD) and Virtual Reality (VR) are integrated in a network system. Another advantage of this proposed graphics system is that it is portable across different operating systems such as Windows 2000 and Linux because the network browser is a common platform in the Internet and Intranet. In fact, this graphics system is capable of sharing resources with each other.